Sovereign Wealth Fund (SWF): Comparison between Indonesia, Singapore and Malaysia - Vincent Guo; Rouli Anita Velentina (Faculty of Law, University of Mataram, 2025)
Sovereign Wealth Fund (SWF) is a state-owned investment institution that is professionally managed to secure financial surpluses, such as natural resource revenues or foreign exchange reserves. SWF aims to support economic stability, income diversification, and long-term development. Since 2020, the Indonesian Government has begun to strengthen the direction of its investment policy by establishing national SWFs, namely the Indonesia Investment Authority (INA) and Daya Anagata Nusantara (Danantara). The establishment of these two institutions is based on regulations such as the Job Creation Law, the BUMN Law, and their implementing regulations. In a global context, the concept of SWF has developed since 1953 and is standardized through the Santiago Principles by the IMF and the International Forum of Sovereign Wealth Funds. This study aims to examine the structure, role, and effectiveness of Indonesia’s SWF, and compare it with the SWF models in Singapore (Temasek and GIC) and Malaysia (Khazanah and 1MDB). Through a comparative approach, this study provides a more comprehensive picture of Indonesia’s position in SWF management and lessons learned from successful and failed SWFs in neighboring countries.